Implementasi Blockchain untuk Transparansi dan Keamanan Rantai Pasok Komponen Elektronik - Rizky Ananda; Kenzi Katon Rinjani (Journal of Engineering and Technological Science, 2025)
The complexity and globalized nature of the electronic components supply chain presents numerous challenges related to transparency, traceability, and security. Current centralized systems are vulnerable to data manipulation and lack real-time visibility, resulting in counterfeiting and inefficiencies. This study aims to explore the implementation of blockchain technology in enhancing transparency and security within the electronic components supply chain. A qualitative method was adopted, involving literature reviews and case studies of leading blockchain adoption in electronics supply management. The research highlights how blockchain's decentralized and immutable ledger offers significant advantages in traceability, counterfeit prevention, and supplier accountability. Results show that incorporating blockchain into supply chain operations reduces data asymmetry and improves stakeholder trust. Furthermore, smart contracts enable automation of verification and payment processes, increasing operational efficiency. The study concludes that blockchain holds transformative potential in securing and optimizing electronic supply chains and recommends further development of interoperable standards and regulatory frameworks.